The heroine construction in Percy Jackson and the Olympians - Augusto Louzada Ferreira de Morais, Guilherme [UNESP]; Soares, C.; Brandao, J. L.; Carvalho, P. C. (Univ Coimbra, 2018)
A priori, we will demonstrate how the Greek women's life was, more specifically in Athens, with the objective of analyzing the heroine's construction on the third book of Percy Jackson and the Olympians, by Rick Riordan, comparing her, consequently, to the Classic heroes, as we can see that the Riordan's female characters also become heroines. We can observe, with the reading of the novel, that the female characters of the American author are equally able to be heroines as his male characters can be heroes, that is, they can defeat any obstacle, defeat any monster (mythic or metaphoric); so, showing that the woman has gained space in society and in the literature.
Keywords: female characters; heroine; Percy Jackson; Rick Riordan